2013
DOI: 10.1136/bmj.f3263
|View full text |Cite
|
Sign up to set email alerts
|

Severe adverse maternal outcomes among low risk women with planned home versus hospital births in the Netherlands: nationwide cohort study

Abstract: Objectives To test the hypothesis that low risk women at the onset of labour with planned home birth have a higher rate of severe acute maternal morbidity than women with planned hospital birth, and to compare the rate of postpartum haemorrhage and manual removal of placenta.Design Cohort study using a linked dataset.Setting Information on all cases of severe acute maternal morbidity in the Netherlands collected by the national study into ethnic determinants of maternal morbidity in the netherlands (LEMMoN stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
80
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 26 publications
6
80
1
6
Order By: Relevance
“…The majority of the findings are similar to those already published in studies undertaken in Brazil and other, developed, countries. 4,6,10,12-13, [23][24][25][26] One of the limitations for discussing the present study's findings is the meager publication of quantitative Brazilian data regarding assistance at home so as to compare the results obtained. [10][11]19 In relation to the sociodemographic characteristics, the age range of the majority of the women was below that found in the international studies (between 30 and 34 years old) [26][27][28][29][30] and in another Brazilian study (30-35 years old).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The majority of the findings are similar to those already published in studies undertaken in Brazil and other, developed, countries. 4,6,10,12-13, [23][24][25][26] One of the limitations for discussing the present study's findings is the meager publication of quantitative Brazilian data regarding assistance at home so as to compare the results obtained. [10][11]19 In relation to the sociodemographic characteristics, the age range of the majority of the women was below that found in the international studies (between 30 and 34 years old) [26][27][28][29][30] and in another Brazilian study (30-35 years old).…”
Section: Discussionmentioning
confidence: 90%
“…International studies have also demonstrated that it is women with higher socioeconomic status who opt for this place to give birth. [3][4]24,29,32 In Brazil, only a small number of home births are attended through the Unified Health System (SUS), being undertaken by the team from the Sofia Feldman Hospital. 33 Other countries support this type of attendance as an integral part of their Health Systems, as is the case with Holland, 4 Australia, 26 Canada, 5 New Zealand 30 and the United Kingdom.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When midwives understand the woman's decision making process regarding place of birth and how to support this process, they are better equipped to facilitate women's decision making in their care and it will allow midwives to move away from a 'home versus hospital birth' debate. 22 In a maternity care system where home-birth is an integrated part of maternity services and where midwives are the main care providers during pregnancy; who aim to maintain the provision of offering homebirth to healthy women, 2,10 it is important to fully understand the features of women's decision making about place of birth 2,10 in order to facilitate this process.…”
mentioning
confidence: 99%